N-doped reduced graphene oxide decorated with Fe3O4 composite: Stable and magnetically separable adsorbent solution for high performance phosphate removal. Issue 3 (June 2019) - Akram, Muhammad Yasir; Ahmed, Saeed; Li, Lingfeng; Akhtar, Naseem; Ali, Safdar; Muhyodin, Ghulam; Zhu, Xiao-Qun; Nie, Jun
Graphical abstract: Highlights: NrGO/Fe3 O4 composite synthesis via greener and facile approach. Phosphate adsorption followed the pseudo second order and Freundlich isotherm. Composite with high adsorption capacity and easy magnetic separation. Abstract: Phosphate deduction is an essential measure compulsory to control eutrophication of water bodies as it hinders disproportionate algae development. Presently existing phosphate removal approaches have several limitations. This study successfully prepared a nitrogen-doped reduced graphene oxide (NrGO) and nitrogen doped reduced graphene oxide decorated with Fe3 O4 nanoparticles as nanocomposite adsorbents which exhibited high capacity and specific affinity towards phosphate. The crystal structure, surface morphology and stability of the adsorbents were investigated by various physiochemical characterizations which revealed the successful doping of nitrogen in GO and uniformly covered by Fe3 O4 nanoparticles. The kinetic study suggests the pseudo second-order better fitted the phosphate adsorption with physisorption and chemisorption. The Freundlich isotherm model better fitted the phosphate adsorption with removal capacity of 169.7 mg g −1 while the reaction mechanism confirms the successful phosphate adsorption by composite material. This study provides an easy synthesis of nitrogen-doped graphene oxide magnetic composite materials with the potential for large scale application.